1994
DOI: 10.1111/j.1471-0528.1994.tb11942.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of placental protein 14 in ectopic pregnancy

Abstract: Objective To determine circulating levels of placental protein 14 (PP14) in complications of early pregnancy. Design Biochemical monitoring of women presenting with vaginal bleeding and/or abdominal pain. Setting An emergency gynaecological ultrasound clinic in a London teaching hospital. Subjects Venous blood samples were obtained from 67 women with normal pregnancy (n= 9), ectopic pregnancy (n= 26) and failed intrauterine pregnancy (n= 32). This group included anembryonic pregnancy (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
1
7
1
Order By: Relevance
“…This was confirmed in a larger cohort of women with a tubal ectopic pregnancy (nZ59; Ruge et al 1992). A comparison of serum PAEP concentrations in women with spontaneous abortion (nZ32) and ectopic pregnancy (nZ26) found that 81% of women with spontaneous abortion had PAEP serum concentration levels within the normal range while 81% of women diagnosed with an ectopic pregnancy had PAEP levels below the fifth percentile of the normal range (Stabile et al 1994). In addition, the lower concentrations of serum glycodelin in ectopic pregnancy was not dependent on tubal status as this difference was maintained in patients with an unruptured tube, a ruptured tube or a tubal miscarriage (Foth & Romer 2003).…”
Section: Glycodelin (Placental Protein-14)mentioning
confidence: 60%
“…This was confirmed in a larger cohort of women with a tubal ectopic pregnancy (nZ59; Ruge et al 1992). A comparison of serum PAEP concentrations in women with spontaneous abortion (nZ32) and ectopic pregnancy (nZ26) found that 81% of women with spontaneous abortion had PAEP serum concentration levels within the normal range while 81% of women diagnosed with an ectopic pregnancy had PAEP levels below the fifth percentile of the normal range (Stabile et al 1994). In addition, the lower concentrations of serum glycodelin in ectopic pregnancy was not dependent on tubal status as this difference was maintained in patients with an unruptured tube, a ruptured tube or a tubal miscarriage (Foth & Romer 2003).…”
Section: Glycodelin (Placental Protein-14)mentioning
confidence: 60%
“…The endometrial protein PP14 plays no known role during normal pregnancy (11), but it has been shown that PP14 levels are subnormal in ectopic pregnancy, perhaps as a result from nidation taking place in the tubal mucosa rather than in the endometrium (12). By (somewhat remote) analogy it might have been expected that PP14 levels in diabetic mothers with vascular disease (White's classes D and F) would differ from those in mothers without, but that was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…Only levels of placental protein 14 [5] and active renin [8] were significantly different comparing ectopic pregnancies and early missed abortions, although no discriminating cut-off level could be determined. Other biochemical markers were not discriminative in the diagnosis of ectopic pregnancy versus early missed abortion, although most of them (excluding creatine kinase) [10][11][12] could differentiate between ectopic and normal intrauterine pregnancy [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…So far, different biochemical markers have been tested for their clinical value in the diagnosis of ectopic versus early intrauterine pregnancy: placental protein 14 [5], prorenin [8], active renin [8], intact hCG [7], free ßhCG [7], progesterone [6,7] and creatine kinase [9][10][11][12]. Only levels of placental protein 14 [5] and active renin [8] were significantly different comparing ectopic pregnancies and early missed abortions, although no discriminating cut-off level could be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation